Promotion of knowledge society through service learning - Mikelić Preradović, Nives; Tuđman, Miroslav; Matić, Sanja (2007)
The goal of this paper is to discuss the relationship between higher education and private&public sector in Croatia, the issues Croatian students face when they get their university degrees and to explore the possibilities of transforming our university into a place that meets the needs of the new economic reality of changing markets and rapidly developing technology. We introduced new educational methodology into our curriculum that transforms the old teaching style and gives student more place to apply theory they learned, while in the same time they think how to solve world problems. Service learning is a methodology where learning occurs when students apply what they learn to community problems and reflect upon their experience as they seek to achieve real objectives for the community. We integrated that methodology with ICT in order to achieve better learning outcomes and we present the first service learning projects in Croatian university in this paper. Service learning should be a well balanced approach to the knowledge society, not only between theoretical knowledge and social needs, but also between education system and social values.
Projekt MZOS
Projekt MZOS
ENG